Valoración del riesgo de lesión del ligamento cruzado anterior en jugadoras de fútbol amateur. [Risk assessment of anterior cruciate ligament injury in female amateur football players]. - Alba Prieto-Valle; Alba Aparicio-Sarmiento; Raquel Hernández-García (Ramón Cantó Alcaraz, 2021)
Few studies have assessed ACL injury risk in women's football using a multifactorial approach. The aim of the present study was to describe the functional deficits and asymmetries manifested by female football players in different tests, in order to perform an integrative analysis of injury risk from different functional and mechanical perspectives. This case study involved 17 female football players from the Spanish Leagues of "Primera Autonómica" and "Preferente Autonómica Femenina", aged from 14 to 23 years old. The tests applied were: OverHead Squat (OHS), Drop Vertical Jump Test (DVJ), Tuck Jump (TJ) and Triple Hop Test (TH). It was found that all players presented better results for the dominant leg, showing a higher mean lateral trunk flexion (TLFA) when landing with the left leg (8.88±5.15º) than when landing with the right leg (7.05±5.40º) in the unipodal DVJ. Furthermore, it was found that a large proportion of the players (41.20%) presented a medium risk of injury in the OHS, as well as a mean medial knee displacement (valgus) in the bipodal DVJ landing (-1.88 cm), while most of them (65%) did not show neuromuscular asymmetries of the lower limb. In conclusion, the players mainly show functional deficits in core stability (CORE) and knee stability to resist and transmit forces in high-risk actions for the ACL such as jump-landing tasks. Therefore, these deficits should be addressed comprehensively with female players.